Mothers of children living with attention deficit hyperactive disorder's experiences of implementing a model to facilitate self-directedness - Lydia Gladness Mdhluli; Annie Temane; Marie Poggenpoel; Chris P.H. Myburgh; Nompumelelo Ntshingila (Elsevier, 2024)
Background: Attention Deficit Hyperactive Disorder (ADHD) in children living in South Africa has led to the development and subsequent implementation and evaluation of a model by mothers aimed at facilitating their self-directedness. Purpose: The study aimed to describe the experiences of mothers of children living with ADHD on implementing the model for the facilitation of self-directedness of the mothers of children living with ADHD. Design and methods: A qualitative, exploratory, descriptive, and contextual research design was utilized. The population included all mothers of children living with ADHD residing in Gauteng. Six mothers of children living with ADHD were purposefully sampled and implemented the model. Participants had to meet an inclusion criteria. Results: The findings revealed that the model had a profound transformational and empowering impact on the mothers and their children's well-being and mental health. These mothers experienced significant improvements in their relationships with their families and other members of the community. The model led to the mothers' self-direction and discovering their purpose in life. Conclusion: The mothers experienced that they had acquired skills and were confident in dealing with challenges met with children living with Attention Deficit Hyperactivity Disorder, as well as developed trust in members of the community and family. Thus, the model led to the mothers' self-direction and discovering their purpose in life as an integral part of mental health.